Recent Trends and Challenges in Smart Cities - Pooja G; Sundar R; Harshini R; Arjuna S; Ram Kumar C (EAI Endorsed Transactions on Smart Cities, 2022)
Smart systems are wanting for smart communities to adapt to restricted spaces and assets across the world. Thus, smart urban communities arose mostly because of exceptionally inventive ICT ventures and markets, and furthermore, they have begun to utilize novel arrangements exploiting the Internet of Things (IoT), huge information and distributed computing innovations to lay out a significant association between every part and layer of a city. Smarter solutions need to be executed to make digital services for economic and social advancement seamlessly reach the occupants in an easy and secure way and encourage them to continue using the amenities. A holistic development rather than just technological advancement is essential for the betterment of Smart lifestyle of the present and future population. This paper attempts to analyze advancements, and the challenges involved in implementing them in various sectors should be executed to make computerized administrations for monetary and social headway flawlessly arrive at the tenants in a simple and secure manner and urge them to keep utilizing the conveniences.
Keywords: smart city; recent trends; challenges